2018
DOI: 10.5093/jwop2018a14
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Relationships in e-Internships: A Matter of the Psychological Contract, Communication and Relational Investment

Abstract: Employment relationships are undergoing rapid change as both organizational, industrial, and technological changes alter the expectations that employees and employers have of each other. Today, technology provides the means for internship programs to be virtual, involving interns and organizations that are geographically distant from one another. These types of computer-mediated internships are also known as virtual or e-internships (Jeske & Axtell, 2013; van Dorp 2008). Two virtual types of such internships e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…The merit of informal (as in more individually agreed and flexible) mentoring arrangements has been demonstrated in a number of studies in the workplace (Singh et al , 2002), training programs (Cobb et al , 2018) and traditional internships (Chao et al , 1992). The informal and thus predominantly flexible and relationship-based nature of these e-internships may be more conducive to developing increasingly natural and rewarding relationships (Jeske and Axtell, 2018a), particularly when the e-internships are of longer duration (e.g. several months to a year) rather than very short (e.g.…”
Section: Mentoring In E-internshipsmentioning
confidence: 99%
“…The merit of informal (as in more individually agreed and flexible) mentoring arrangements has been demonstrated in a number of studies in the workplace (Singh et al , 2002), training programs (Cobb et al , 2018) and traditional internships (Chao et al , 1992). The informal and thus predominantly flexible and relationship-based nature of these e-internships may be more conducive to developing increasingly natural and rewarding relationships (Jeske and Axtell, 2018a), particularly when the e-internships are of longer duration (e.g. several months to a year) rather than very short (e.g.…”
Section: Mentoring In E-internshipsmentioning
confidence: 99%
“…Many employers miss out on a valuable opportunity to reduce early attrition during or shortly after onboarding, by not considering the role of onboarding experiencing (Bauer, 2010). Previous work has already shown that relational investment and communication can be critical for the relationship with and retention of virtual interns (Jeske and Axtell, 2018). It is important to review how onboarding can prevent potential attrition of new hires – by assessing which signals are being sent through the organisers, the interactions, and the representatives that show up (or do not).…”
Section: The Onboarding Experience: Immediate Costs Vs Long-term Bene...mentioning
confidence: 99%
“…The current qualitative data from respondents highlight concerns regarding sporadic communication and communication occurring primarily via asynchronous email. Jeske and Axtell (2018) emphasise that technology is not the problem for online communication, rather it is the nature of the communication that needs to be Perceptions of online internships carefully considered, with multiple communication options recommended. The importance of adequate support was also highlighted, from both workplace and academic supervisors or mentors.…”
Section: Factors Influencing Perception Of Internshipsmentioning
confidence: 99%